POLYPHENOLS AND HUMAN HEALTH- A REVIEW - MEHVESH MUSHTAQ; S.M.WANI (International Journal of Pharma and Bio Sciences, 2013)
Flavonoids, perhaps the most important single group of phenolics in foods, comprise a group of over 4000 C15 aromatic plant compounds with multiple substitution patterns. Anthocyanins are members of the flavonoid group of phytochemicals, a group predominant in teas, wines, fruits, vegetables, nuts, olive oil, cocoa, and cereals. The colorful anthocyanins are the most recognized, visible members of the bioflavonoid phytochemicals with proven human health benefits of myriad nature. Anthocyanin isolates and anthocyanin-rich mixtures of bioflavonoids provide protection from DNA cleavage, estrogenic activity, enzyme inhibition, boosting production of cytokines, anti-inflammatory activity, lipid peroxidation, decreasing capillary permeability and fragility, and membrane strengthening. To add to the importance of anthocyanin pigments in human health, both in vitro and in vivo research trials have amply demonstrated their marked ability to reduce cancer cell proliferation and to inhibit tumor formation. The capacity of anthocyanin pigments to interfere with the process of carcinogenesis seems to be linked to multiple potential mechanisms of action including inhibition of cyclooxygenase enzymes and potent antioxidant potential. Another feather in cap is the role of anthocyanins in cardiovascular disease protection which is strongly linked to oxidative stress protection.